The Impact of Stimulation Intensity on Spatial Discrimination with Multi-Pad Finger Electrode - Jovana Malešević (MDPI AG, 2021)
Multi-pad electrotactile stimulation can be used to provide tactile feedback in different applications. The electrotactile interface needs to be calibrated before each use, which entails adjusting the intensity to obtain clear sensations while allowing the subjects to differentiate between active pads. The present study investigated how the stimulation intensity affects the localization of sensations using a multi-pad electrode placed on a fingertip and proximal phalange. First, the sensation, localization, smearing and discomfort thresholds were determined in 11 subjects. Then, the same subjects performed a spatial discrimination test across a range of stimulation intensities. The results have shown that all thresholds were significantly different, while there was no difference in the threshold values between the pads and phalanges. Despite the subjective feeling of spreading of sensations, the success rates in spatial discrimination were not significantly different across the tested stimulation intensities. However, the performance was better for distal compared to proximal phalange. Presented results indicate that spatial discrimination is robust to changes in the stimulation intensity. Considering the lack of significant difference in the thresholds between the pads, these results imply that more coarse adjustment of stimulation amplitude (faster calibration) might be enough for practical applications of a multi-pad electrotactile interface.